Can Stabilization and Inhibition of Aquaporins Contribute to Future Development of Biomimetic Membranes? - To, Janet (2016)
In recent years, the use of biomimetic membranes that incorporate membrane proteins, i.e., biomimetic-hybrid membranes, has increased almost exponentially. Key membrane proteins in these systems have been aquaporins, which selectively permeabilize cellular membranes to water. Aquaporins may be incorporated into synthetic lipid bilayers or to more stable structures made of block copolymers or solid-state nanopores. However, translocation of aquaporins to these alien environments has adverse consequences in terms of performance and stability. Aquaporins incorporated in biomimetic membranes for use in water purification and desalination should also withstand the harsh environment that may prevail in these conditions, such as high pressure, and presence of salt or other chemicals. In this respect, modified aquaporins that can be adapted to these new environments should be developed. Another challenge is that biomimetic membranes that incorporate high densities of aquaporin should be defect-free, and this can only be efficiently ascertained with the availability of completely inactive mutants that behave otherwise like the wild type aquaporin, or with effective non-toxic water channel inhibitors that are so far inexistent. In this review, we describe approaches that can potentially be used to overcome these challenges.